Reinventing the House of Lords for the XXIst century - Anne Cousson (Revue LISA)
An entirely unelected Upper House looks, at first sight, to sit uneasily with a XXIst century democracy. In this context, the House of Lords has had to carve out its own role in the British constitutional settlement. Since the reforms of the beginning of the XXIst century, its legitimacy and positions have shifted. This article focuses on a case study of four bills in order to assess what is the place of the House of Lords today. The Lords have become a specialised House focusing on issues of civil liberties. This has meant that they have built a role of counter-power to the executive, while still maintaining strategies of cooperation with the House of Commons in law-making.